The mediating role of psychological resilience in the relationship between physical exercise and sense of security among left-behind junior high school students: multi-group comparative analysis of only children and children with siblings - Xia, Qifei; Liu, Qi; Qin, Guoyou (Frontiers in Psychology, 2024)
Background: This study aims to explore the mediating role of psychological resilience in the relationship between physical exercise and the sense of security among junior high school students, with a particular focus on variations based on only-child status. Methods: A survey was conducted among 649 left-behind junior high school students in Gansu Province, China, utilizing the Physical Activity Rating Scale-3 (PARS-3), Security Questionnaire (SQ), and Resilience Scale for Chinese Adolescents (RSCA). Results: Among the participants, the mean scores for physical exercise, psychological resilience, and sense of security were 40.78±29.49, 51.14±10.08, and 55.75±14.35, respectively. A significant positive correlation was observed between physical exercise and sense of security (r = 0.210, P < 0.01), physical exercise and psychological resilience (r = 0.164, P < 0.01), and psychological resilience and sense of security (r = 0.443, P < 0.01).Mediation analysis revealed that psychological resilience partially mediates the effect of physical exercise on the sense of security, accounting for 33.9% of the total effect. Multi-group analysis indicated significant differences in this mediating effect between only children and children with siblings, with a stronger predictive role of psychological resilience for the sense of security among non-only children. Conclusion: Participation in physical exercise can promote the improvement of sense of security through the individual power factor of improving the psychological resilience of left-behind junior high school students, and this improvement effect is more significant for non-only children.